Optimising the dosing of antibiotics: Colistin and vancomycin updates - Reklia Solomon; Soumya Thambi; Soonu Udani (Wolters Kluwer Medknow Publications, 2015)
Multidrug resistant gram-negative nosocomial infection in intensive care units has resulted in an increased use of antibiotics like Colistin and Tigeicycline that the end user may have little experience with. Mechanism of drug resistance, when understood, leads to the correct choice and combination of antibiotics. Understanding the phamacokinetics of Colistin and proper dosing with a correct loading dose is vital to treatment success. Issues regarding renal toxicity may be important factors in critically ill children and much of the dosing is extrapolated form adult studies.